PLANNING OF DOMESTIC WASTEWATER FACILITIES (CASE STUDY: BABAKAN VILLAGE, CIPARAY DISTRICT, BANDUNG REGENCY) - Deni Rusmaya; Evi Afiatun; Muhammad Al Hadad (Journal of Community Based Environmental Engineering and Management, 2021)
Babakan Village has a problem that there is still a lack of facilities for wastewater. This condition can be seen from the access to the toilets of 2436 households; only around 1506 families have access to family/ shared latrines and 625 households that meet technical requirements. For this reason, this plan is useful for increasing access and meeting community needs for domestic wastewater treatment facilities in the study area. This planning stage begins with a survey and sanitation inspection to determine 3 priority areas for handling. Determinants of this priority area use the method of scoring and weighting the risk. The weighting results put sub village 02 with a score of 2.3, sub village 05 with a score of 2.25, and RW 10 with a risk value of 2 as the priority area for planning handlers. Primary data collected will be used as a consideration for determining the technology to be applied. The technology chosen for processing is the communal septic tank for people who do not have treatment. In contrast, for the washing bath, toilet with a biofilter unit for people who do not have wastewater infrastructure.